Evaluasi Kondisi Sarana Sanitasi yang Disediakan Dinas Kebudayaan dan Pariwisata dan Tingkat Kepuasan Wisatawan Pantai Depok, Bantul, Yogyakarta, Tahun 2016 - Layly Alinda Saraswati; Indah Werdiningsih; Purwanto Purwanto (Poltekkes Kemenkes Yogyakarta, 2016)
The degree of community health can be affected by environmental and human factors. Environ-mental health efforts are aimed to create a quality of healthy environment through the application of public place sanitation, one of which is to provide sanitation facilities in tourism spots. Accord-ing to the preliminary test, various problems regarding to the condition of sanitation facilities and the satisfaction level of tourists were found in Depok Beach of Bantul. The purpose of this study was to determine the condition of the sanitation facilities provided by the Office of Culture and Tourism on that beach as well as the tourists’ satisfaction. This study used survey method with cross sectional design and the results were analyzed descriptively. There were 100 tourists se-lected as the respondents and the instrument used to collect the data was the sanitation inspect-ion questionnaire. Based on the questionnaire, the sanitation condition will be declared ”healthy worthy” if gain minimum score of 650, out of the 1000 maximum score. The results showed that the sanitation condition in Depok Beach is deserve to have “healthy worthy” level since gaining a score of 675. The results also found that the number of tourists who very satisfied with the condi-tion was 1 respondent 91 %); satisfied, 8 respondents (8 %); fairly satisfied, 51 respondents (51 %); not satisfied, 40 respondents (40 %); and none who is very dissatisfied. The condition of sa-nitation facilities in the beach that “healthy worthy” will increase customer satisfaction.